Impact of performance-based financing on primary health care services in Haiti - Zeng, W. [et al] (2013)
Evaluates firstly the separate impact of performance-based financing (PBF) and international support on primary health care (PHC) service delivery; secondly the combined impact of PBF and technical assistance on PHC delivery and finally the costs of PBF implementation in Haiti.